Media and the making of migrants - Palmary, Ingrid (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Hegde, Radha Sarma (2016) Mediating migration. Cambridge: Polity Press. ISBN 978-0-7456-4632-9 hbk. Pages x + 161 This book is about how the migration experience is mediated by new technologies. This mediation is clearly articulated in the introductory chapter which outlines the mediating role that media, technology and other forms of communication plays in the migration experience. As Hegde argues: “New technologies enable both the disciplining and self-expression of migrant communities worldwide. Devices, technologies and various types of changing media platforms are being widely used by migrants to reinvent and redefine identity” (p 11).